The Kinematics Analysis of a Novel 3-DOF Cable-Driven Wind Tunnel Mechanism - Yao Yu; Wu Hongtao (Journal of Robotics)
The kinematics analysis method of a novel 3-DOF wind tunnel mechanism based on cable-driven parallel mechanism is provided. Rodrigues' parameters are applied to express the transformation matrix of the wire-driven mechanism in the paper. The analytical forward kinematics model is described as three quadratic equations using three Rodridgues' parameters based on the fundamental theory of parallel mechanism. Elimination method is used to remove two of the variables, so that an eighth-order polynomial with one variable is derived. From the equation, the eight sets of Rodridgues' parameters and corresponding Euler angles for the forward kinematical problem can be obtained. In the end, numerical example of both forward and inverse kinematics is included to demonstrate the presented forward-kinematics solution method. The numerical results show that the method for the position analysis of this mechanism is effective.